Coastal Natural and Nature-Based Features: International Guidelines for Flood Risk Management - Bridges, Todd S.; Smith, Jane McKee; King, Jeffrey K.; Simm, Jonathan D.; Dillard, Maria; deVries, Jurre; Reed, Denise; Piercy, Candice D.; van Zanten, Boris; Arkema, Katie; Swannack, Todd; de Looff, Harry; et al. (Frontiers in Built Environment, 2022)
Natural and nature-based features (NNBF) have been used for more than 100 years as coastal protection infrastructure (e.g., beach nourishment projects). The application of NNBF has grown steadily in recent years with the goal of realizing both coastal engineering and environment and social co-benefits through projects that have the potential to adapt to the changing climate. Technical advancements in support of NNBF are increasingly the subject of peer reviewed literature, and guidance has been published by numerous organizations to inform technical practice for specific types of nature based solutions. The International Guidelines on Natural and Nature Based Features for Flood Risk Management was recently published to provide a comprehensive guide that draws directly on the growing body of knowledge and practitioner experience from around the world to inform the process of conceptualizing, planning, designing, engineering, and operating NNBF. These Guidelines focus on the role of nature-based solutions and natural infrastructure (beaches, dunes, wetlands and plant systems, islands, reefs) as a part of coastal and riverine flood risk management. In addition to describing each of the NNBF types, their use, design, implementation, and maintenance, the guidelines describe general principles for employing NNBF, stakeholder engagement, monitoring, costs and benefits, and adaptive management. An overall systems approach is taken to planning and implementation of NNBF. The guidelines were developed to support decision-makers, project managers, and practitioners in conceptualizing, planning, designing, engineering, implementing, and maintaining sustainable systems for flood risk management. This paper summarizes key concepts and highlights challenges and areas of future research.